Review – Didactics of mathematics. A scientific discipline - Gjone, Gunnar (NOMAD Nordic Studies in Mathematics Education, 1995)
Review Biehler, R., Scholz, R.W., Strässer, R. & Winkelmann, B. (eds.) (1994). Didactics of Mathematics as a Scientific Discipline. (Mathematics Education Library, Volume 13). Dordrecht, NL: Kluwer Academic Publishers, 467p.